The political economy of terrorism - Enders, Walter 1948- (Cambridge University Press, 2006)
The Political Economy of Terrorism, first published in 2006, presents a widely accessible approach to the study of terrorism that combines economic methods with political analysis and realities. It applies economic methodology - theoretical and empirical - with political analysis to the study of domestic and transnational terrorism. Included in the treatment are historical aspects of the phenomenon, a discussion of watershed events, the rise of modern-day terrorism, examination of current trends, the dilemma of liberal democracies, evaluation of counterterrorism, and analysis of hostage incidents. Rational-actor models of terrorist and government behavior and game-theoretic analysis are presented for readers with no prior theoretical training. Where relevant, the authors display graphs using the data set International Terrorism: Attributes of Terrorist Events (ITERATE), and other data sets